Primary surgery versus no surgery in synchronous metastatic breast cancer: patient-reported quality-of-life outcomes of the prospective randomized multicenter ABCSG-28 Posytive Trial - Bjelic-Radisic, V. (BMC Cancer, 2020)
BACKGROUND: The ABCSG-28 trial compared primary surgery followed by systemic therapy versus primary systemic therapy without surgery in patients with de novo stage IV BC. The present report describes QoL results of this trial. METHODS: Ninety patients with primary operable MBC were randomised to surgery of the primary tumor followed by systemic therapy or to primary systemic therapy without surgery. QoL analyses covering the results at baseline, 6,12,18 and 24 months follow up of 79 (88%) patients, was assessed with the EORTC QLQ-C30 and QLQ-BR23 questionnaires. RESULTS: There were no statistically significant differences in any of the scales of the QLQ-C30 and QLQ-BR23 questionnaires between the two groups over the time. Baseline global health status and physical functioning were predictors for OS (patients with a higher score lived longer (p=0.0250, p=0.0225; p=0.0355, p=0.0355)). Global health status, social functioning scale, breast symptoms and future perspective were predictors for longer TTPd (p=0.0244; p=0.0140, p=0.020; p=0.0438, p=0.0123). Patients in both arms reported significant improvement on the emotional functioning scale. Cognitive functioning decreased over time in both groups. Younger women had clinically relevant better physical and sexual functioning scores (p=0.039 and 0.024). CONCLUSION: Primary surgery does not improve nor alter QoL of patients with de novo stage IV BC. Global health status and physical functioning were predictors for OS and could be use as additional marker for prediction of OS and TTTd in patients with de novo stage IV BC. TRIAL REGISTRATION: The trial is registered on clinicaltrial.gov (NCT01015625, date of registration:18/11/2009).